Conflitos de fronteira : produção do espaço em Feira de Santana – do rural ao urbano na Mantiba - Souza, Diego Almeida de (2016)
The present dissertation entitled Border Conflicts: Space Production in Feira de Santana – from the Rural to the Urban in Mantiba aims at analyzing the relationship field-city in Feira de Santana, explaining the transformation of the rural area into an urban one by means of the Complementary Law No. 075 of 2013, taking as a reference Mantiba. So, the specific objects of this work are to analyze the implications that are due to the transformation of a rural area into an urban one, thinking about the specificities of Mantiba dwellers everyday and to identify the urban area expansion of Feira de Santana between 1938-2016, analyzing the relationship field-city. In the same work, we adopt the regressive-progressive method developed by Lefebvre (1978), which is composed of three points. The adoption of this method occurs to take account of its constant departure from the current time toward the past, not only to explain it, but, overall, to enlighten the current processes pointing to the future. It is concluded that the real estate capital, in various nuances, was the key reason for the Complementary Law No. 075 of 2013, created by the municipal executive power, without any discussion, debate or public audiences preceding the complementary law project remittance to Feira de Santana Town Hall.